Design of high breakdown voltage GaN-based vertical HFETs with p-GaN island structure for power applications. (September 2015) - Du, Jiangfeng; Liu, Dong; Bai, Zhiyuan; Liu, Yong; Yu, Qi
Abstract: In order to achieve higher breakdown voltage ( BV ) and low on-resistance ( RON ), a GaN-based vertical heterostructure field effect transistor with p-GaN islands (GaN PI-VHFET) is proposed in this paper. By introducing the p-GaN islands, the electric field distribution along the buffer layer could be optimized obviously and the breakdown voltage of the GaN-based PI-VHFETs could be improved significantly compared with the conventional GaN devices. Moreover, the GaN PI-VHFET shows greatly advantages of the trade-off between RON and BV . Simulation results show that the breakdown voltage and on-resistance of the device with a p-GaN island are 3188 V and 2.79 mΩ cm 2, respectively. And the average breakdown electric field reaches as high as 212.5 V/μm. Compared with the typical GaN vertical heterostructure FETs without p-GaN islands, the breakdown voltage increases more than 50% while on-resistance keeps low.